Effects of spatial heterogeneity and material anisotropy on the fracture pattern and macroscopic effective toughness of Mancos Shale in Brazilian tests. Issue 8 (19th August 2017) - Na, SeonHong; Sun, WaiChing; Ingraham, Mathew D.; Yoon, Hongkyu
Abstract: For assessing energy‐related activities in the subsurface, it is important to investigate the impact of the spatial variability and anisotropy on the geomechanical behavior of shale. The Brazilian test, an indirect tensile‐splitting method, is performed in this work, and the evolution of strain field is obtained using digital image correlation. Experimental results show the significant impact of local heterogeneity and lamination on the crack pattern characteristics. For numerical simulations, a phase field method is used to simulate the brittle fracture behavior under various Brazilian test conditions. In this study, shale is assumed to consist of two constituents including the stiff and soft layers to which the same toughness but different elastic moduli are assigned. Microstructural heterogeneity is simplified to represent mesoscale (e.g., millimeter scale) features such as layer orientation, thickness, volume fraction, and defects. The effect of these structural attributes on the onset, propagation, and coalescence of cracks is explored. The simulation results show that spatial heterogeneity and material anisotropy highly affect crack patterns and effective fracture toughness, and the elastic contrast of two constituents significantly alters the effective toughness. However, the complex crack patterns observed in the experiments cannot completely be accounted for by either an isotropic or transversely isotropic effective medium approach. This implies that cracks developed in the layered system may coalesce in complicated ways depending on the local heterogeneity, and the interaction mechanisms between the cracks using two‐constituent systems may explain the wide range of effective toughness of shale reported in the literature. Key Points: Brazilian tests with DIC reveal the tensile strain of Mancos Shale due to anisotropic microlithofacies and mineralogical heterogeneity Phase‐field modeling results show that spatial heterogeneity and material anisotropy highly affect crack patterns and effective fracture toughness Crack coalescence and interaction mechanisms using two‐constituent models explain the wide spectrum of effective toughness of shale observed in the literature Plain Language Summary: Shale has become increasingly important for emerging energy technology problems in the subsurface such as unconventional gas and oil recovery, geologic storage of CO2, enhanced oil recovery, and nuclear waste disposal. In particular, geomechanical behavior of shale rocks is important to assess crack initiation and propagation which can be important for energy‐related activities including fluid injection/extraction and fracturing. In this work, an indirect tensile test on Mancos Shale was performed, and the evolution of the strain field and growth of the fractures were experimentally obtained using digital imaging process. Experimental results reveal the significant impact of small features and laminations on the characterization of crack patterns. Based on the experimental observations, numerical modeling has been conducted to simulate fracture processes under various conditions mimicking the experimental setup. Simulation results show that spatial heterogeneity and material anisotropy reflecting microstructural attributes highly affect crack patterns and effective fracture toughness, and the contrast of elasticity of the two constituents (stiff and soft materials) was sufficient to significantly alter the effective toughness. Overall, this work provides a robust workflow to explain the wide spectrum of effective toughness of shale reported in the literature.